Fog Computing: Overview and Research Challenges - Ahuja, A (International Journal of Computer Sciences and Engineering, 2025)
With the increasing use of Internet and its services leads to the generation where availability of data has become boundless. The abundant flow of data due to the advent of IoTs is not new and for storing such huge amount of data paved the way for the technology like cloud computing. But with cloud computing still some issues need to be resolved such as high latency, network bandwidth, network congestion, security and others that cannot be compromised in case of real time applications. ‘Fog computing’ introduces a new dimension to the way cloud works as it focuses on the provisioning of resources and services at the edge of the network that means closer to end devices and hence there is less delay in processing client’s request in distributed environment. So in this perspective it is heading the way to cloud computing paradigm. Its evolution is not for replacing cloud computing but to complement in such a manner that its potential can be realized and utilized in an effective manner. This paper highlights the fog computing technology concept and gives an insight details in terms of its characteristics, and the related work done in prospect of challenges.